How cryo-EM is revolutionizing structural biology. Issue 1 (January 2015) - Bai, Xiao-chen; McMullan, Greg; Scheres, Sjors H.W
Highlights Cryo-EM single-particle analysis reaches near-atomic resolution for a wide variety of specimens. Direct electron detectors yield images of unprecedented quality. New movie-processing methods correct for beam-induced sample movements. New classification methods separate images of different structures.